A Brief History of Pacemaking - DiFrancesco, Dario (Frontiers in Physiology, 2020)
Cardiac pacemaking is a most fundamental cardiac function, thoroughly investigated for decades with a multiscale approach at organ, tissue, cell and molecular levels, to clarify the basic mechanisms underlying generation and control of cardiac rhythm. Understanding the processes involved in pacemaker activity is of paramount importance for a basic physiological knowledge, but also as a way to reveal details of pathological dysfunctions useful in the perspective of a therapeutic approach. Among the mechanisms involved in pacemaking, the “funny” (If) current has properties most specifically fitting the requirements for generation and control of repetitive activity, and has consequently received the most attention in studies of the pacemaker function. Present knowledge of the basic mechanisms of pacemaking and the properties of funny channels has led to important developments of clinical relevance. These include: 1) the successful development of heart rate-reducing agents, such as ivabradine, able to control cardiac rhythm and useful in the treatment of diseases such as coronary artery disease, heart failure and tachyarrhythmias; 2) the understanding of the genetic basis of disorders of cardiac rhythm caused by HCN channelopathies; 3) the design of strategies to implement biological pacemakers based on transfer of HCN channels or of stem cell-derived pacemaker cells expressing If, with the ultimate goal to replace electronic devices. In this review, I will give a brief historical account of the discovery of the funny current and the development of the concept of If-based pacemaking, in the context of a wider, more complex model of cardiac rhythmic function.